Development and assessment of the Alberta Context Tool - Birdsell Judy M; Cummings Greta G; Squires Janet E; Estabrooks Carole A; Norton Peter G (BMC, 2009)
Abstract Background The context of healthcare organizations such as hospitals is increasingly accepted as having the potential to influence the use of new knowledge. However, the mechanisms by which the organizational context influences evidence-based practices are not well understood. Current measures of organizational context lack a theory-informed approach, lack construct clarity and generally have modest psychometric properties. This paper presents the development and initial psychometric validation of the Alberta Context Tool (ACT), an eight dimension measure of organizational context for healthcare settings. Methods Three principles guided the development of the ACT: substantive theory, brevity, and modifiability. The Promoting Action on Research Implementation in Health Services (PARiHS) framework and related literature were used to guide selection of items in the ACT. The ACT was required to be brief enough to be tolerated in busy and resource stretched work settings and to assess concepts of organizational context that were potentially modifiable. The English version of the ACT was completed by 764 nurses (752 valid responses) working in seven Canadian pediatric care hospitals as part of its initial validation. Cronbach's alpha, exploratory factor analysis, analysis of variance, and tests of association were used to assess instrument reliability and validity. Results Factor analysis indicated a 13-factor solution (accounting for 59.26% of the variance in 'organizational context'). The composition of the factors was similar to those originally conceptualized. Cronbach's alpha for the 13 factors ranged from .54 to .91 with 4 factors performing below the commonly accepted alpha cut off of .70. Bivariate associations between instrumental research utilization levels (which the ACT was developed to predict) and the ACT's 13 factors were statistically significant at the 5% level for 12 of the 13 factors. Each factor also showed a trend of increasing mean score ranging from the lowest level to the highest level of instrumental research use, indicating construct validity. Conclusions To date, no completely satisfactory measures of organizational context are available for use in healthcare. The ACT assesses several core domains to provide a comprehensive account of organizational context in healthcare settings. The tool's strengths are its brevity (allowing it to be completed in busy healthcare settings) and its focus on dimensions of organizational context that are modifiable. Refinements of the instrument for acute, long term care, and home care settings are ongoing.